Sistem Akuntansi Pemberian Kredit Agunan Rumah Dalam Mendukung Pengendalian Internal Pemberian Kredit - Dera, Firman; Masiaga, Novaliastuti; Rahman, Zubaidah; Hasan, Wahyudin (Gorontalo Accounting Journal, 2024)
This research aims to explain and analyze how the Accounting System for Providing Home Collateral Credit at PT. Bank Tabungan Negara, Tbk Gorontalo Branch Office. The method used in the research is a qualitative descriptive review. PT. Bank Tabungan Negara, Tbk Gorontalo Branch Office has implemented an accounting system for granting home mortgage creditÂ  well and meets the internal control elements and is in accordance with established standards, and is supported by an E-Loan system which can provide convenience in the credit granting process and more effective and efficient credit decision making from the credit granting system.